Gamma Spectrometry results for the 134Cs nuclear parameters - de Almeida , Maria Candida Moreira; Delgado , José Ubiratan; da Silva , Ronaldo Lins; Poledna , Roberto (Seven Editora, 2023)
134Cs are produced directly as a fission product (low yield) and too obtained by neutron capture from 133Cs non-radioactive. The National Laboratory for Ionizing Radiation Metrology (LNMRI/IRD/CNEN) of Rio de Janeiro performed standardization of this radionuclide. A solution of 134Cs radionuclide was purchased from a commercial supplier for nuclear parameters determination such as activity and emission probabilities of some of its energies. 134Cs is a beta gamma emitter with 754 days of half-life. This radionuclide is used as a standard in environmental, water, and food control. It is also important to germanium detector calibration The gamma emission probabilities were determined mainly for some energies of the 134Cs by the efficiency curve method and the most uncertainties obtained were around 1.5 %. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-090